2016
DOI: 10.1590/1808-1657000272013
|View full text |Cite
|
Sign up to set email alerts
|

In vitro interaction of bovine herpesvirus 1 with uterine tube epithelial cells and oocytes

Abstract: The aims of this study were to assess in vitro if bovine oocytes and oviductal epithelial cells from slaughterhouses for in vitro fertilization use may be infected with bovine herpesvirus 1; to analyze whether the treatment with trypsin according to the International Embryo Transfer Society guideline is efficient to inactivate the bovine herpesvirus 1; to morphologically study the virus-oocyte interaction through optical microscopy. In this study, Madin Darby Bovine Kidney (MDBK) cells that were co-cultured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This agrees with observations by D' Angelo (1998), who found that both bovine oocytes matured in vitro with BoHV-1 and those matured in the absence of the virus had indistinguishable morphology. This finding was also verified by Gonçalves et al (2015), who also did not observe any morphological alterations in infected oocytes.…”
Section: Discussionsupporting
confidence: 64%
“…This agrees with observations by D' Angelo (1998), who found that both bovine oocytes matured in vitro with BoHV-1 and those matured in the absence of the virus had indistinguishable morphology. This finding was also verified by Gonçalves et al (2015), who also did not observe any morphological alterations in infected oocytes.…”
Section: Discussionsupporting
confidence: 64%